Efeito sistêmico da terapia de fotobiomodulação em lesão causada pelo veneno de bothrops jararacussu sobre biomarcadores da hemorragia e mionecrose - Pisete, Flávia Regina Ferreira Soares (2019)
Accidents with Bothrops genus snakes are recurrent in the world. Those snakes are capable to produce venom that causes severe and complex systemic and local effects in the victim. Serotherapy, the first-choice treatment, despite neutralizing some systemic effects, is ineffective in neutralizing the local response caused by the venom. Then, it is essential to look after alternative therapies for serotherapy, that helps in the local damages of the venom. Several studies have demonstrated the effectiveness of the photobiomodulation in the treatment of lesions caused by venom of snakes of the genus Bothrops. Therefore, the objective of this study is to increase the knowledge photobiomodulation actions using LED (Light Emitting Diode) on the biomarkers of myonecrosis and hemostasis disorders caused by venom of the snake Bothrops jararacussu. In this context, four experimental groups of rats genus Wistar were used (n = 20 / group) and divided into control groups and the group that were injected with the venom of Bothrops jararacussu (30 μL / mL) in the gastrocnemius muscle and treated at local with LED wavelength 660 nm, energy density 5.8 J / cm2 and potency of 160 mW. The animals were sacrificed for blood collection by vena cava puncture at times of 1, 3, 6 and 24 hours (n = 5 / time; n = 20 / group) after inoculation of the venom. Experiments with the dose 300 μg of venom were performed for collection at times 1 and 6h (n=5/time; n=10/group). Measurements of platelets, prothrombin time, partial thromboplastin time and fibrinogen, TGO, LDH, CPK, FAL were be performed to assess the effect of LED on those biomarkers. The results showed that LED had a protective effect only for TGO and CPK.